La auto-etnografía y el método biográfico como mediaciones de la comprensión: indagaciones en primera persona - Muñoz Cano, Jeyson Alejandro (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The objectivity in journalism and the reflexivity in anthropology demarcate territories approached from ethnography and reporting. The latter tries not to “interfere too much” in order to not adulterate the essence of the story, while the former believes it has the “magical potion” for comprehending the place we occupy and the place we are assigned in the contexts investigated. In both cases, what is is evidence is that personal charge, this filter that catalizes first-person narrative, permeates our researchers. In this sense this essay describes in detail a research experience in which theory and method are reconfigurated on the go, based ou autoethnography and on the biographical method as orienting reference for certain research processes in social sciences.